A forensic procedure based on GC–MS, HPLC-HRMS and IBA to analyse products containing sildenafil or the doping agent oxandrolone. (June 2022) - Mestria, Serena; Chiari, Massimo; Romolo, Francesco Saverio; Odoardi, Sara; Strano Rossi, Sabina
Abstract: The market of falsified or sub-standard medical products is a global scale phenomenon. This issue affects a wide range of medications, including life-saving medical products. In high-income countries the most falsified products are those defined "lifestyle", which include foremost anabolic steroids and phosphodiesterase 5 inhibitors. The spread of these products in the last years has been possible also because of their online purchase, since they can be bought anonymously and without any medical supervision or prescription. Their use can pose a serious threat for public health, especially because often are manufactured without adherence to quality standards. This leads to final products containing active ingredients different from those declared, at the wrong or unknown dose and contaminated with metals, synthesis by-products and other chemical substances. In this work, we present results on characterisation of illegal pharmaceutical products and doping agents by combining different techniques: chromatography coupled to mass spectrometry for organic analysis and accelerator-based nuclear analytical techniques, such as ion beam analysis (IBA), for elemental analysis. Three IBA techniques, namely PIXE (particle induced X-ray emission), PIGE (particle induced gamma-ray emission) and EBS (elastic backscattering spectrometry) were used in external beam mode to provide an elemental characterisation of the as-is material, placed simply in front of the proton beam, thus avoiding the need of preparing them with pre-analytical steps and greatly enhancing the measurement throughput. Several elements (F, Mg, Al, Si, P, S, Cl, K, Ca, Ti, V, Mn, Fe, Co, Ni, Cu, Zn, Br and Sr) were identified in the analysed products. External beam IBA measurements provided the quantitative elemental characterisation of the illegal pharmaceutical products and doping agents under study, complementary to the organic analysis results by chromatography and mass spectrometry thus allowing a rapid (a few minutes) and non-destructive direct assessment of the material for forensic purposes. For the first time IBA results from doping products are reported and further analysis by IBA involving two different accelerator laboratories (one in Italy and one in Brazil) allowed the comparison of results obtained on the same pharmaceutical product. Starting from the results obtained in our study, the actualisation of new research plans should be evaluated, which could lay the foundation for a classification system of illegal pharmaceutical products, doping products. and other substances, based on chromatography, mass spectrometry and IBA measurements; this could allow drawing inferences about the common characteristics of these substances, e.g. provenience of bulk materials, site of production etc. With this purpose, results obtained from two samples of the same pharmaceutical product by IBA in two different accelerator laboratories (one in Italy and one in Brazil) are compared. Highlights: IBA results from doping products are reported for the first time. IBA methods combined with GC-MS and HPLC-HRMS were used to study illegal pharmaceutical products. External beam IBA provided the concentrations of several elements in tablets without any sample preparation. GC-MS and HPLC-HRMS provide the characterisation of the active compounds and of organic by-products. IBA results obtained in two laboratories were compared, confirming some criteria for detecting illegal medicines.